2015
DOI: 10.1037/adb0000109
|View full text |Cite
|
Sign up to set email alerts
|

Can marijuana make it better? Prospective effects of marijuana and temperament on risk for anxiety and depression.

Abstract: Increases in marijuana use in recent years highlight the importance of understanding how marijuana affects mental health. Of particular relevance is the effect of marijuana use on anxiety and depression given that marijuana use is highest among late adolescents/early adults, the same age range in which risk for anxiety and depression is the highest. Here we examine how marijuana use moderates the effects of temperament on level of anxiety and depression in a prospective design in which baseline marijuana use a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…Half (50%) of the participants identified as transgender women, 38% as cisgender men, and 12% as transgender men. Participant median age was 26 years (range [18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Resultsmentioning
confidence: 99%
“…Half (50%) of the participants identified as transgender women, 38% as cisgender men, and 12% as transgender men. Participant median age was 26 years (range [18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Resultsmentioning
confidence: 99%
“…As a secondary analysis, the current study was unable to assess for marijuana use problems, which may be uniquely related to anxiety and use of marijuana as a coping mechanism. Additionally, further studies have proposed various other factors that may complicate the pattern between marijuana use and anxiety, including parental attitudes and tension reduction expectancies (Foster, Ecker, Zvolensky, & Buckner, 2015), an individual's temperament in terms of harm avoidance versus novelty seeking (Grunberg, Cordova, Bidwell, & Ito, 2015), distress tolerance (Semcho et al, 2016), and behavioral avoidance (Buckner, Zvolensky, Farris, & Hogan, 2014). Thus, the relationship between marijuana use and anxiety remains quite complex, and these findings certainly add further complexity to our current understanding of this dynamic.…”
Section: Discussionmentioning
confidence: 99%
“…Other research that has suggested marijuana may attenuate the risk for depression and anxiety has noted that this relationship was largely subject to individual temperament (Grunberg et al, 2015). Also, individuals may seek out more formal anxiety treatment regardless of whether or not they are using marijuana to cope.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have explored the effect of cannabis use on the course of specific anxiety disorders. For example, individuals who used cannabis were more prone to have earlier onset of panic attacks (Zvolensky, Bernstein, Marshall, & Feldner, ), elevated intensity of anxiety symptoms during panic attacks (Szuster, Pontius, & Campos, ), and increased severity of anxiety symptoms (Grunberg, Cordova, Bidwell, & Ito, ). In addition, it has been suggested that pathological use of cannabis (i.e., cannabis use disorders [CUDs]) may be associated with increased risk for the onset of anxiety disorders (Zvolensky et al., ) and may predict poorer outcome of anxiety disorders (Essau, Conradt, & Petermann, ).…”
Section: Introductionmentioning
confidence: 99%